Digital Whole Slide Imaging Compared With Light Microscopy for Primary Diagnosis in Surgical Pathology: A Multicenter, Double-Blinded, Randomized Study of 2045 Cases. - Borowsky, Alexander D.; Glassy, Eric F.; Wallace, William Dean; Kallichanda, Nathash S.; Behling, Cynthia A.; Miller, Dylan V.; Oswal, Hemlata N.; Feddersen, Richard M.; Bakhtar, Omid R.; Mendoza, Arturo E.; Molden, Daniel P.; Saffer, Helene L.; et al. (Archives of Pathology & Laboratory Medicine, 2020)
Context.--The adoption of digital capture of pathology slides as whole slide images (WSI) for educational and research applications has proven utility. Objective.--To compare pathologists' primary diagnoses derived from WSI versus the standard microscope. Because WSIs differ in format and method of observation compared with the current standard glass slide microscopy, this study is critical to potential clinical adoption of digital pathology. Design.--The study enrolled a total of 2045 cases enriched for more difficult diagnostic categories and represented as 5849 slides were curated and provided for diagnosis by a team of 19 reading pathologists separately as WSI or as glass slides viewed by light microscope. Cases were reviewed by each pathologist in both modalities in randomized order with a minimum 31-day washout between modality reads for each case. Each diagnosis was compared with the original clinical reference diagnosis by an independent central adjudication review. Results.--The overall major discrepancy rates were 3.64% for WSI review and 3.20% for manual slide review diagnosis methods, a difference of 0.44% (95%CI, -0.15 to 1.03). The time to review a case averaged 5.20 minutes for WSI and 4.95 minutes for glass slides. There was no specific subset of diagnostic category that showed higher rates of modality-specific discrepancy, though some categories showed greater discrepancy than others in both modalities. Conclusions.--WSIs are noninferior to traditional glass slides for primary diagnosis in anatomic pathology.